2005
DOI: 10.1002/app.21438
|View full text |Cite
|
Sign up to set email alerts
|

Development of thermoregulating textile materials with microencapsulated phase change materials (PCM). II. Preparation and application of PCM microcapsules

Abstract: Melamine-formaldehyde microcapsules containing eicosane were prepared by in situ polymerization. The characterization of the microcapsules, including the particle size and size distribution, morphology, thermal properties, and stability, was carried out. The prepared microcapsules were added to polyester knit fabrics by a conventional pad-dry-cure process to develop thermoregulating textile materials. The morphology, thermal properties, and laundering properties of the treated fabrics were also investigated. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
117
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 221 publications
(128 citation statements)
references
References 8 publications
2
117
0
4
Order By: Relevance
“…For example, improved thermal insulation can be provided by nonwovens made with thin hollowed fibers 1 and can be made thermo-adaptive with two-way shape memory alloys like nickel-titanium [11]. Better thermoregulation inside the garment is sought with phase change materials [12], either encapsulated [13] or incorporated in a matrix [14]. Other solutions use external power, e.g., for liquid coolant circulation [15] or with Peltier cells embedded in the textile [16].…”
Section: Materials For Protection Against Heat and Flamementioning
confidence: 99%
“…For example, improved thermal insulation can be provided by nonwovens made with thin hollowed fibers 1 and can be made thermo-adaptive with two-way shape memory alloys like nickel-titanium [11]. Better thermoregulation inside the garment is sought with phase change materials [12], either encapsulated [13] or incorporated in a matrix [14]. Other solutions use external power, e.g., for liquid coolant circulation [15] or with Peltier cells embedded in the textile [16].…”
Section: Materials For Protection Against Heat and Flamementioning
confidence: 99%
“…If the shape stabilization is performed with a metallic or a carbon based material, this also leads to an increase of the overall thermal conductivity [27,28]. TES systems based on PCMs find applications in buildings [29,30], hot/cold water storage [31], solar thermal power plants [32], smart thermoregulating textiles [25,33], and thermal management of electronic devices [22]. In most of these applications, the TES function is performed by a dedicated added module, containing PCMs.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that using octadecylamine (ODA) to modify MEPCM particles resulted in a significant increase of the dispersing extent (DE) and the electrophoresis velocity of the particles in TCE (about 4 and 20 times more than that of unmodified). Shin et al [30], [31] prepared melamine-formaldehyde microcapsules containing Eicosane for textile materials.…”
Section: In Situ Polymerizationmentioning
confidence: 99%
“…Kim and Kim [77] indicated that the heat of fusion of waterborne polyurethane (WBPU) /octadecane-coated nylon fabrics were much higher than those of the control nylon fabric and WBPU-coated nylon fabrics; and the nylon fabrics coated with WBPU/octadecane blends have cooler touch sensation compared with nylon fabrics and WBPU-coated nylon fabrics. Shin et al [30] fabricated M/F microcapsules with eicosane for textile application. The microcapsules had high latent heat and the treated fabrics retained 40 % of their heat storage capacity after five launderings.…”
Section: Textile Applicationsmentioning
confidence: 99%